Policy Analysis of Permendikbudristek Number 30 of 2021: Dynamics of Higher Education Resistance and Rethinking the Best Solutions - Khoiri, Ikhwanul; Kafa, Muhammad Zidny (LPPM Universitas Jambi, 2024)
This paper aims to find out the root causes of the implementation of Permendikbudristek Number 30 of 2021 using boundary analysis, forecasting, and policy recommendations for these problems using the May Method. Sexual violence is still high in the Higher Education Environment. Therefore, the Ministry of Research and Technology issued Permendikbudristek Regulation Number 30 of 2021 concerning Prevention and Handling of Sexual Violence (PPKS) in the Higher Education Environment. However, in its implementation, various problems have arisen. So it is necessary to study more deeply the formal problems of the implementation for the improvement of the PPKS policy in the future. The method used is qualitative with an online interview system and secondary data collection. Based on the scoring (number of problems) and further review, the formal problem of implementing Permendikbudristek Number 30 of 2020 is that there are different value perspectives on this regulation by Higher Education Institutions (university) or Higher Education leaders. At the forecasting stage, it was found that the ambiguity of the diction of the rules in Permendikbudristek could cause ongoing resistance from some university leaders and certain NGOs/community groups. Policy recommendations are made using the May method with limited manipulation for resistant university, moderate manipulation for neutral/orderly university, and extensive manipulation for university supporting the implementation of Permendikbudristek through policy variables: University leadership, Task Force establishment, Task Force human resource assistance, and Task Force funding.